Construction and Validation of the 21 Item Fitness-to-Drive Screening Measure Short-Form - Sherrilene Classen; Shabnam Medhizadah; Sergio Romero; Sergio Romero; Mi Jung Lee (Frontiers Media S.A., 2018)
Introduction: The Fitness-to-Drive Screening Measure is a free online screening tool that detects at-risk older drivers, however, it's 20 min administration time may render the 54-item tool less than optimal for clinical use. Thus, this study constructed and validated a 21-item FTDS Short-Form (FTDS-SF).Method: This mixed methods study used 200 proxy rater responses and older driver on-road assessments. We conducted a Rasch analysis to examine information at the level of the item and used content validity index scores to select items. Using a receiver operator characteristics curve we determined the concurrent validity of the FTDS-SF to on-road outcomes.Results: Twenty-one items were selected for the FTDS-SF. The area under the curve = 0.72, indicated the FTDS-SF predicted on-road outcomes with acceptable accuracy. Still, 68 drivers were misclassified.Conclusion: The FTDS-SF may reduce administration time, while still yielding acceptable psychometric properties. Yet, caution needs to be executed in clinical decision making as the measure is overly specific.